Social Perception Among Husbands of Women Diagnosed with Primary Infertility: A Qualitative Study in Semarang City, Central Java - Dewi Puspitaningrum; Mohammad Zen Rahfiludin; Mohammad Irsam (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Primary infertility is a significant reproductive health issue that not only affects women but also their husbands. However, most health education programs still focus predominantly on women, leaving men’s perceptions underexplored. Understanding husbands’ social perceptions is crucial for developing inclusive interventions that address both partners’ needs. This study aimed to explore the social perceptions of husbands whose wives have primary infertility, focusing on their views regarding health education, psychological well-being, and support systems. Methods: This qualitative study used a phenomenological approach and was conducted in Semarang City, Central Java. Participants were recruited purposively, consisting of husbands whose wives were clinically diagnosed with primary infertility. Data were collected through in-depth interviews using a semi-structured guide and analyzed thematically. Results: Findings showed that husbands of women diagnosed with primary infertility were aged > 45 years old 13 persons (65%) and had education levels ranging bachelor school 9 persons (45%). They worked most as private sector employees 13 persons (65%). Most lived with their wives 11 persons (55%). Health education programs mostly targeted the wives, with minimal psychological support for husbands. Education on healthy behaviors was delivered generally, and mental health topics were addressed only upon request. No program specifically designed for husbands existed. Several husbands had low knowledge and attitudes about infertility and felt excluded from reproductive health discussions. Conclusion: Current reproductive health education programs inadequately address the needs of husbands of women with primary infertility. Developing husband-inclusive interventions that integrate physical and psychological health components is essential.